The Role of Fiscal Policy in Strengthening the Resilience of The National Economy (Fiscal Case Study During the Covid-19 Pandemic) - Farah Aunti Sholihah; Badriyatul Ulya; Husnul Mirzal; Shally Nur Rasyida; Siti Zubaidah (Ijtimā iyya Journal of Muslim Society Research, 2022)
Due to the Covid-19 pandemic, Indonesia's economic growth rate reached negative 5.32 percent. In this problem, Indonesia manages its economic stabibility with fiscal instruments. This study aims to determine the role of fiscal policy in strengthening the resilience of the national economy during the Covid-19 pandemic. This research is a type of literature research that uses analytical techniques with a content analysis method that strengthens the role of the government, especially in fiscal policy in overcoming the Covid-19 pandemic in Indonesia